O sistema eleitoral brasileiro: uma análise sobre a questão da desproporcionalidade - Carvalho, Eder Aparecido de (2005)
Emphasizing the existing disproportions in the Brazilian electoral system, the present work analyses some of the elements which distort its proportionality such as, the formula for converting votes into seats - highest average (d'Hondt version) -, the clause of electoral exclusion, the electoral coalitions, and the unequal allocation of seats to each Brazilian state. Additionally, this work shows through simulations that an electoral system, which is free of clauses and coalitions and followed by redistribution of electoral district boundaries, leads to a considerable reduction in the country s existing electoral disproportion.